2014
DOI: 10.1021/jp4125342
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Constitution of Compressed Strontium Polyhydrides

Abstract: The structures of the strontium polyhydrides, SrH n with n > 2, under pressure are studied using evolutionary algorithms coupled with density functional theory calculations. A number of phases with even n are found to be thermodynamically stable below 150 GPa. Particularly interesting is the SrH 4 stoichiometry, which comprises the convex hull at 50, 100, and 150 GPa. Its hydrogenic sublattice contains H 2 and H − units, and throughout the pressure range considered, it adopts one of two configurations which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 111 publications
6
82
0
Order By: Relevance
“…Calculations carried out with a variant of the configuration interaction (CI) method have shown that H − 3 is asymmetric with H-H distances measuring 0.75 and 2.84 Å, and the barrier between the two possible minima is symmetric, with H-H distances measuring ∼1.06 Å [60]. Symmetric and asymmetric H − 3 motifs have been observed in polyhydrides containing Na [21], K [28], Rb [27], Cs [29], Sr [23,32] and Ba [31]: one example is the RbH 5 phase illustrated in Fig. 1(c) [27].…”
Section: How To Metallize With An Electropositive Elementmentioning
confidence: 99%
See 4 more Smart Citations
“…Calculations carried out with a variant of the configuration interaction (CI) method have shown that H − 3 is asymmetric with H-H distances measuring 0.75 and 2.84 Å, and the barrier between the two possible minima is symmetric, with H-H distances measuring ∼1.06 Å [60]. Symmetric and asymmetric H − 3 motifs have been observed in polyhydrides containing Na [21], K [28], Rb [27], Cs [29], Sr [23,32] and Ba [31]: one example is the RbH 5 phase illustrated in Fig. 1(c) [27].…”
Section: How To Metallize With An Electropositive Elementmentioning
confidence: 99%
“…(c) Pressure induced overlap of the non-bonding and anti-bonding H − 3 bands, as in RbH 5 [27]. (d) Formation of a one-dimensional hydrogenic chain, as in SrH 6 [32]. These mechanisms occur in hydrogenic sublattices that contain the following hydrogenic motifs:…”
Section: How To Metallize With An Electropositive Elementmentioning
confidence: 99%
See 3 more Smart Citations